IMMUNOLOGICAL STUDY OF CORONARY ARTERY DISEASE ASSOCIATED WITH DIABETES MELLITUS TYPE II IN IRAQI PATIENTS - Al-okhedi, Mundher Jabbar; Qais Al-ani, Mohammed; Rasheed, Marrib N (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to investigate the association between proinflammatory cytokines in special, the interleukin-6 (IL-6), and insulin-like growth factor (IGF-1) levels in coronary artery disease (CAD) and type 2 diabetes mellitus (T2DM). Methods: This study was conducted from November 2017 to March 2018 in Anbar, Iraq. We studied a total of 90 individuals (46 men and 44 women) aged between 20 and 87 years. The samples were divided into four groups: CAD patients (n=23), T2DM patients (n=23), coronary artery disease and type 2 diabetes together in the same patient (n=23), and control group (n=21). The concentrations of IL-6 and IGF-1 were determined using a commercially available enzyme-linked immune sorbent assay. Results: The results of the present study showed that there were elevated serum levels of IL-6 and low levels of IGF-1 in all the tested groups, compared with the control. The difference was statistically significant at p<0.05. The results showed a positively correlated between IL-6 and IGF-1 in the CAD group and T2DM group, while it was a negative correlation between serum levels of IL-6 and IGF-1 in the T2DM+CAD group. Conclusion: Elevated levels serum of IL-6 predicts the development of CAD and T2DM. These data support a possible role for inflammation in diabetogenesis and complication of the cardiovascular disease. There is an inverse relationship between the levels serum of IGF-1 and increased risk of CAD and development of T2DM.